Peningkatan Kesadaran Hukum Mengantisipasi Terjerat Investasi Bodong Di Desa Sumberagung, Kecamatan Plumpang, Kabupaten Tuban - Sulistyani Eka Lestari; Grahadi Purna Putra; Muhari (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2022)
Communities often experience and have the potential for problems regarding fraudulent investments, even though the Government of the Republic of Indonesia has made a policy that is set forth in a regulation or legislation needed to anticipate that the community will avoid the trap of fraudulent investment but until now there are still many people who being a victim of fraudulent investment, this is proof that there is still a lack of public legal awareness in anticipating fraudulent investment traps and a lack of knowledge about how to invest in accordance with the provisions of the laws and regulations that apply in Indonesia.Given the lack of legal awareness in the community about the importance of this matter, it is necessary to provide legal counseling and provide education to the community, especially residents of Sumberagung Village, Plumpang District, Tuban Regency to be able to understand every provision and/or statutory regulation related to investment and investment as an effort to increase legal awareness in anticipating and avoiding fraudulent investment traps and how to deal with them.Community Service Activities (PPM) are carried out by conducting legal counseling and/or providing education through the lecture method. The lecture method is used to explain laws and regulations related to investment and investment as a means of preventing and overcoming fraudulent investments that can harm society financially.Community service activities as a whole can be said to be good and successful, seen from the success of the target number of training participants (100%), the achievement of training objectives (75%), the achievement of planned material targets (80%), and the participants' ability to master the material ( 75%).